PENGARUH LATIHAN PENDEKATAN TAKTIK TERHADAP KETERAMPILAN PASSING CONTROL CABANG OLAHRAGA FUTSAL - Ghiyas Muhammad; Mochamad Zakky Mubarok; Yudhi Kharisma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by several students who still made mistakes in performing passing and control skills in futsal extracurricular activities. This study aims to determine the effect of tactical approach training on passing control skills in futsal at MTs Miftahul 'Ulum Arjawinangun, Cirebon Regency. This quantitative research used a one-group pretest-posttest design with a sample of 30 students selected through purposive sampling. Data were collected using passing control skills tests and documentation. The results showed that the application of the tactical approach significantly improved students' passing control skills. When viewed from the pretest average of (2.81) and posttest average of (6.33), with a pretest standard deviation of (0.73) and a posttest standard deviation of (1.46) then the results of the pretest variance value (0.54) and the results of the posttest variance value of (2.15). The results of the normality test can be concluded that the pretest t_count (0.551) is greater than L_table (0.173) and the posttest t_count (0.475) is greater than L_table (0.173). This means that Ho is rejected and Ha is accepted. The hypothesis test then obtained a sig value of (0.00) < (0.05), so the data is declared significant. Therefore, there is an effect of tactical approach training on passing control skills in futsal.